2016
DOI: 10.3390/nu8080475
|View full text |Cite
|
Sign up to set email alerts
|

Beverage Intake Assessment Questionnaire: Relative Validity and Repeatability in a Spanish Population with Metabolic Syndrome from the PREDIMED-PLUS Study

Abstract: We assess the repeatability and relative validity of a Spanish beverage intake questionnaire for assessing water intake from beverages. The present analysis was performed within the framework of the PREDIMED-PLUS trial. The study participants were adults (aged 55–75) with a BMI ≥27 and <40 kg/m2, and at least three components of Metabolic Syndrome (MetS). A trained dietitian completed the questionnaire. Participants provided 24-h urine samples, and the volume and urine osmolality were recorded. The repeatabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…16,22,40,41 Because of the importance of accurately recording drinks consumption, several fluid-specific questionnaires have been validated in other languages. 13,42 In Greece, a similar tool was developed some years ago, 43 evaluating water intake from liquid, solid foods and water, as well as urine, faeces and sweat water loss. However, because of its different aim, it is not a quick assessment tool, as the DFQ.…”
Section: Discussionmentioning
confidence: 99%
“…16,22,40,41 Because of the importance of accurately recording drinks consumption, several fluid-specific questionnaires have been validated in other languages. 13,42 In Greece, a similar tool was developed some years ago, 43 evaluating water intake from liquid, solid foods and water, as well as urine, faeces and sweat water loss. However, because of its different aim, it is not a quick assessment tool, as the DFQ.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date have indicated that 24-h recalls significantly underestimate intake when compared to a 7-day diary [37]. A few beverage-specific questionnaires have been developed with promising early results [32, 33], and a recent study in adults has demonstrated the validity and reliability of a 7-day fluid record using total body water turnover [34]. …”
Section: State Of the Art In The Assessment Of Total Fluid Intakesmentioning
confidence: 99%
“…Using both the urine osmolality and the 24-h urine volume analysis, 66% of individuals were categorised in the same or adjacent quintile, demonstrating a reasonably good level of questionnaire validity. The questionnaire also demonstrated good repeatability; the difference between baseline measurement of total fluid intake and the measurement after 6 months and 1 year were not significant [ 32 ]. The Water Balance Questionnaire was adapted for use with Greek pregnant women and when compared to urine hydration indices, it was considered to be valid [ 33 ].…”
Section: State Of the Art In The Assessment Of Total Fluid Intakesmentioning
confidence: 99%
“…To our knowledge, no previous studies have validated a beverage intake questionnaire in a chronic kidney disease population. In fact, to date, we identified only three beverage questionnaire validation studies, and these were evaluated in a general healthy population [ 6 , 17 , 18 ]. Hedrick et al [ 6 ] validated a questionnaire against food records ( r = 0.456, p < 0.001); whereas, questionnaires by Ferreira-Pago et al [ 17 ] and Malisova et al [ 18 ] were validated against 24-h urine volume ( r = 0.447, p = 0.0003; r = 0.29, p = 0.015, respectively) and osmolality ( r = −0.447, p = 0.0005; r = −0.30, p = 0.010, respectively).…”
Section: Discussionmentioning
confidence: 99%